Preparation of hollow microsphere@onion-like solid nanosphere MoS2 coated by a carbon shell as a stable anode for optimized lithium storage. Issue 1 (1st December 2015) - Guo, Bangjun; Yu, Ke; Song, Haili; Li, Honglin; Tan, Yinghua; Fu, Hao; Li, Chao; Lei, Xiang; Zhu, Ziqiang
Abstract : Hollow microsphere@solid nanosphere MoS2 was synthesized via a facile one-step hydrothermal process, then coated with carbon shell for use as an anode material with enhanced lithium storage performance. Abstract : A one-step hydrothermal method was successfully used to fabricate hollow microsphere@onion-like solid nanosphere MoS2 . Then the as-prepared sS-MoS2 was decorated with a carbon shell using dopamine as a carbon source by a facile route, resulting in hollow microsphere@onion-like solid nanosphere MoS2 decorated with carbon shell (sS-MoS2 @C). A synergistic effect was observed for the two-component material, leading to new electrochemical processes for lithium storage, with improved electroconductivity and structural soundness, triggering an ascending capacity upon cycling. The as-prepared sS-MoS2 @C exhibits optimized electrochemical behaviour with high specific capacity (1107 mA h g −1 at 100 mA g −1 ), superior high-rate capability (805 mA h g −1 at 5000 mA g −1 ) and good cycling stability (91.5% of capacity retained after 100 cycles), suggesting its potential application in high-energy lithium-ion batteries.